2008
DOI: 10.1590/s0100-06832008000200025
|View full text |Cite
|
Sign up to set email alerts
|

Frações de fósforo em solo adubado com fosfatos em diferentes modos de aplicação e cultivado com milho

Abstract: (6) RESUMO O histórico de uso e o manejo da adubação influenciam a capacidade de suprimento de P pelo solo. Neste trabalho, foram avaliadas as frações de P num Argissolo Vermelho da região do Cerrado, adubado com fosfatos de reatividade distinta, em diferentes modos de aplicação e cultivado com milho durante três safras. A área, que já havia sido adubada em épocas passadas, estava coberta por braquiária. O delineamento experimental foi o de blocos casualizados com quatro repetições, num esquema fatorial 4 x 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 11 publications
6
17
0
13
Order By: Relevance
“…These results are in agreement with those obtained by Pavinato et al (2009), who reported that in a clay-loam textured Typic Hapludox, with a history of phosphate fertilization and annual crops, P was accumulated in moderately labile fractions extracted by 0.1 and 0.5 mol L -1 NaOH throughout the soil profile, which can be used by crops in cases of lack of available P (Gatiboni et al, 2007;Santos et al, 2008).…”
Section: P Fractionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are in agreement with those obtained by Pavinato et al (2009), who reported that in a clay-loam textured Typic Hapludox, with a history of phosphate fertilization and annual crops, P was accumulated in moderately labile fractions extracted by 0.1 and 0.5 mol L -1 NaOH throughout the soil profile, which can be used by crops in cases of lack of available P (Gatiboni et al, 2007;Santos et al, 2008).…”
Section: P Fractionsupporting
confidence: 92%
“…This may be due to higher Fe oxide contents extracted by dithionitecitrate-bicarbonate and ammonium oxalate (Table 1). These data agree with those of Santos et al (2008) who, in a sandy Typic Hapludalf soil with clayey texture and phosphate fertilization (180 kg P 2 O 5 ha -1 ) in three growing seasons of corn, found a predominance of residual P in the 0-20 cm layer. Figure 1 shows the accumulated P fractions found in the three layers of all three studied areas.…”
Section: Phosphorus Fractionssupporting
confidence: 92%
See 1 more Smart Citation
“…conventional tillage system (CTS) areas and native forest areas with oxisol, Silva et al (2000) found lower values for Fed, Feo and Fep for CTS in two areas but, for NTS, found values for Fed and Feo similar to those observed in native forest areas. In comparing an NTS area (26 years of management) with the same soil in a CTS area, Inda et al (2010) found a 5% reduction in the level of Fed in the NTS and attributed this to reductive dissolution and/or Fe complexation.…”
Section: Introductionmentioning
confidence: 76%
“…The levels of extractible iron in the 2-mm fraction were determined by atomic absorption spectrophotometry after extraction with a solution of sodium dithionite-citrate-bicarbonate (Fed), according to the method described by Schulze (1984), and with a solution of acid ammonium oxalate 0.2 mol L -1 (Feo). We also determined the iron forms extracted by sodium pyrophosphate (Fep) to yield iron complexed with the organic fraction of the soil.…”
Section: Methodsmentioning
confidence: 99%